90Sr CONDITION IN THE EAST CHINA SEA AND NORTH PACIFIC - Muslim . (JOURNAL OF COASTAL DEVELOPMENT, 2006)
The condition of 90Sr concentration in the East China Sea and North Pacific closed to the Japanese island has been measured from 3 – 31 July 2000. There were differences condition of 90Sr concentration in the those locations. The concentration of 90Sr detected in the surface East China Sea and North Pacific ranged 0.44–1.32 mBq/ℓ and 0.66-1.38 mBq/ℓ respectively. Generally, the condition 90Sr concentration in the East China Sea was lower than in the North Pacific. The highest 90Sr concentration occurred in the off shore of North Pacific, because the 90Sr in the open sea is dominantly from nuclear weapon testing and nuclear power plant accident (Chernobyl) rather than other resources, and it take long time to precipitate into the bottom. Kuroshio and Taiwan-Tsushima warm current systems influenced importantly in distribution of 90Sr concentration in the East China Sea beside other physical factors such as fishing activity. These currents were not strong enough to stimulate increasing 90Sr concentration in the coastal region of North Pacific close to the Japanese islands.